A Study of Purchasing Behavior of Thai Tourists towards Street Food in Wonnapha Beach Area, Chonburi Province - ศรศักดิ์, ถิรพิทย์; โนรี, ภัทราวุฒิ; ช่องงาม, มะลิวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study the consumption behavior of street food purchases of Thai tourists in the Wonnapha Beach area, Chonburi Province, classified by demographic characteristics. The quantitative research used a questionnaire from a sample group of Thai tourists in the Wonnapha Beach area, Chonburi Province. The results were analyzed using a statistical program, with a statistical significance level set at 0.05, using the mean (x̅) and standard deviation (S.D.).From the personal characteristics on the behavior of consuming street food of Thai tourists in the area of ​ Wonnapa, Chonburi Province. The classification by gender and age that are different in the overall has no different opinions on behavior. As for the classification by education level and income that are different in the overall, there are different opinions on behavior.Considering each aspect, it was found that the taste of the food was the aspect that Thai tourists gave the most importance. Next were the variety of the food menu, cleanliness, food price, payment methods, and the amount of food purchased, respectively, and the location of the restaurant was the aspect that gave the least importance, accounting for a percentage, with statistical significance at the .05 level.